The Efficient Implementation of Hybrid Power Plants in Indonesia - Perdiansyah, Farhan; Fitriana, Eka Tiara Nur; Aziema, Nur; Maharani, Permata Putri; Khoerunnisa, Fitri; Winarno, Nanang (Indonesian Journal of Multidiciplinary Research, 2021)
The energy crisis is a serious issue that all countries around the world are dealing with, particularly the energy sources used to generate electricity. There are numerous alternative energy sources available in nature, such as solar energy, wind energy, and so on. Wind and solar energy as hybrid energy sources are thought to be promising in electric generation technology. Hybrid Power Plants can also be used to address the issue of limited electrical energy supply in Indonesia's remote areas. The purpose of this study is to describe the effectiveness of the hybrid power plants implementation in Indonesia. The study was conducted using the narrative literature review method. It can be inferred that the purpose of developing this hybrid technology, among others, is to obtain more efficient electrical energy generation by combining the advantages of two or more types of power generation systems that work in an integrated manner as a compact system. The produced electric energy can be stored in the battery. In terms of use, the produced direct current (DC) is converted into alternating current (AC) using the inverter system prior to distribution to consumers. Therefore, this hybrid power plant is suitable to be implemented in Indonesia.